WRITING LEFT - Pinnock, Don. ([S.l.])
1 online resource
Keywords: This book presents a detailed study of the political journalism of Ruth First - an independent thinker and a headstrong journalist who stood her ground in a male-dominated liberation movement. A product of information gathering which began in South Africa in 1986 (at a time when discussing communism exposed one to the possibility of imprisonment without trial), the subject matter in this book discusses her unwavering commitment and contribution to a free press. Print editions not for sale in Sub-Saharan Africa. This book is part of Routledge's co-published series 30 Years of Democracy in South Africa, in collaboration with UNISA Press, which reflects on the past years of a democratic South Africa and assesses the future opportunities and challenges.